Potential of Bacillus pumilus to directly promote plant growth - Dobrzyński, Jakub; Jakubowska, Zuzanna; Dybek, Barbara (Frontiers in Microbiology, 2022)
Plant Growth-Promoting Bacteria (PGPB) are a promising alternative to conventional fertilization. Among the spore-forming bacteria of the phylum Firmicutes, one of the most interesting PGPB strains is Bacillus pumilus. It is a bacterial species that inhabits a wide range of environments and shows resistance to abiotic stresses. So far, several PGPB strains of B. pumilus have been described, including B. pumilus LZP02, B. pumilus JPVS11, B. pumilus TUAT-1, B. pumilus TRS-3, and B. pumilus EU927414. These strains have been shown to produce a wide range of phytohormones and other plant growth-promoting substances. Therefore, they can affect various plant properties, including biometric traits, substance content (amino acids, proteins, fatty acids), and oxidative enzymes. Importantly, based on a study with B. pumilus WP8, it can be concluded that this bacterial species stimulates plant growth when the native microbiota of the inoculated soil is altered. However, there is still a lack of research with deeper insights into the structure of the native microbial community (after B. pumilus application), which would provide a better understanding of the functioning of this bacterial species in the soil and thus increase its effectiveness in promoting plant growth.